The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pts.1973
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring and Microstructuring of Materials from a Single Agropolymer for Sustainable MAP Preservation of Fresh Food

Abstract: The main objective of the present work was to determine whether a single agropolymer [wheat gluten (WG)] could fit the modified atmosphere packaging (MAP) requirements of a range of six different fresh produce in key terms of oxygen permeation (PeO2) and CO2/O2 permselectivity (S) values. The required properties for optimal packaging of fresh fruits and vegetables were first evaluated using the Tailorpack MAP modelling software (UMR IATE, Montpellier, France) with packaging dimensions and respiratory and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…Several authors reported the fabrication of multilayered films by depositing intercalated layers of anionic sodium montmorillonite clay and cationic polymer on a polymer substrate yielding materials with extremely good barrier properties. 53,59,[62][63][64][65] Another means of improving the barrier properties of a polymer film is the deposition of a thin, metal or metal-oxide or organic-based coating. Nanocoatings have a thickness in the nanometre range and comparatively infinite size in the other dimensions that are deposited on the surface of a substrate (e.g.…”
Section: Nanomaterial-polymer Composites For Improved Barrier Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported the fabrication of multilayered films by depositing intercalated layers of anionic sodium montmorillonite clay and cationic polymer on a polymer substrate yielding materials with extremely good barrier properties. 53,59,[62][63][64][65] Another means of improving the barrier properties of a polymer film is the deposition of a thin, metal or metal-oxide or organic-based coating. Nanocoatings have a thickness in the nanometre range and comparatively infinite size in the other dimensions that are deposited on the surface of a substrate (e.g.…”
Section: Nanomaterial-polymer Composites For Improved Barrier Propertiesmentioning
confidence: 99%
“…Although still in their infancy, the amount of research performed on these materials is significant, as can be seen for the review articles by Siqueira et al 74 and more recently by Li et al 75 Research is ongoing to overcome these inherent shortcomings of biopolymer-based packaging materials, with nanotechnology being one avenue of exploration. 51,[53][54][55][56]59,65,66,68 Nanomaterialbiopolymer materials have the potential to match many of the properties required for packaging applications; hence, their use could increase the potential for biopolymer use.…”
Section: Special Case: Bio-based Materialsmentioning
confidence: 99%
“…Firstly, it relied on the validation of the virtual MAP model which has been done in the past on endives and tomatoes (Charles et al, 2003(Charles et al, , 2005Cagnon et al, 2012Cagnon et al, , 2013. Secondly, it has been done using a classical use-cases testing procedure of the functionalities associated with the flexible bipolar querying system presented in Section 3.3.…”
Section: Validation Of the Flexible Querying Systemmentioning
confidence: 99%
“…This approach is especially important when developing packaging made from biodegradable materials, which becomes a new trend, as their limited barrier properties, possibly optimized using smart and/or composite multilayer material (Guillaume et al, 2010), can turn out to be an asset to extend shelf life of respiring foods (Cagnon et al, 2012;Guilbert et al, 2011;Guillaume et al, 2008). To facilitate MAP design, mathematical models, so-called virtual MAP, have been developed by researchers working in this field to design passive (Mahajan et al, 2007;Souza-Gallagher and Mahajan, 2013) or active MAP (Cagnon et al, 2012;Charles et al, 2003Charles et al, , 2005 for fresh and fresh-cut fruits and vegetable. Online applications are today available for free (www.tailorpack.com) or charged access (www.packinmap.com).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional post harvest techniques used until now need to be improved meeting the request of a greener supply chain system, consequently also the modified atmosphere packaging (MAP), that is well known to improve the shelf life of many fresh fruits and vegetables reducing their respiration rate (Kader and Barrett, 2005;Caner et al, 2008;Mangaraj et al, 2009;Soltani et al, 2015;Zang et al, 2015;Blanco-Diaz et al, 2016), must to be considered in this new prospective. The sustainability of the MAP technique to preserve fresh fruits is today mainly associated to the use on new materials (Almenar et al, 2008;Cagnon et al, 2013;Briano et al, 2015;Mistriotis et al, 2016) whose mechanical and chemical characteristics are well described (Cano et al, 2015), but more studies are necessary about their interaction with the contained fruits especially in terms of fermentative compounds, resulting by the post harvest maturity processes, that affect the acceptability of the consumers.…”
Section: Introductionmentioning
confidence: 99%